2010
DOI: 10.1038/nature09338
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a quality-control mechanism for mRNA 5′-end capping

Abstract: The 7-methylguanosine cap structure at the 5′-end of eukaryotic mRNAs is a critical determinant of their stability and translational efficiency1–3. It is generally believed that 5’-end capping is a constitutive process that occurs during mRNA maturation and lacks the need for a quality control mechanism to ensure its fidelity. We recently reported that the yeast Rai1 protein has pyrophosphohydrolase activity towards mRNAs lacking a 5’-end cap4. Here we show that, in vitro as well as in yeast cells, Rai1 posses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
206
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(218 citation statements)
references
References 36 publications
8
206
3
1
Order By: Relevance
“…29 Thus, its implication in this alternative nuclear mRNP QC is conceivable. In contrast, our data indicate clearly that Rai1p, the Rat1p cofactor specialized in removing unmethylated caps, 23,24 is not involved in the production of uncapped HXK1 mRNPs since no transcript recovery could be observed in the rai1D strain (Fig. 5A).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…29 Thus, its implication in this alternative nuclear mRNP QC is conceivable. In contrast, our data indicate clearly that Rai1p, the Rat1p cofactor specialized in removing unmethylated caps, 23,24 is not involved in the production of uncapped HXK1 mRNPs since no transcript recovery could be observed in the rai1D strain (Fig. 5A).…”
Section: Discussioncontrasting
confidence: 52%
“…This possibility was explored first by performing RT-qPCR measurements with RNAs extracted from cells lacking the catalytic subunit of the decapping enzyme (dcp2D) or lacking Rai1p (rai1D), a known cofactor of Rat1p that possesses also a decapping endonuclease activity specifically toward unmethylated caps. 24 As shown in Fig. 5A, the removal of Dcp2p leads to a substantial rescue of the HXK1 transcripts under Rho inducing conditions (mRNA level around 60% in dcp2D as compared to the 30% level for the wild-type strain), whereas the absence of Rai1p did not lead to any rescue effect.…”
Section: Rho-induced Aberrant Hxk1 Mrnps Are Decapped Prior To Degradmentioning
confidence: 95%
“…S3B), we used a dcp2Δ xrn1Δ rai1Δ triple mutant expressing a Rai1 mutant with amino acid substitution E221A D223A, which corresponds to the E199A D201A mutation in Schizosaccharomyces pombe Rai1 that was shown previously to inactivate the catalytic activity (Fig. S3A) (26). We observed that the 5′ RLM-RACE signals from ERG13, CWP2, and RPS31 were still detectable in a dcp2Δ xrn1Δ rai1EADA mutant (Fig.…”
Section: ′ P Ends Located In Intronsmentioning
confidence: 99%
“…Previous work has identified the Rai1 protein as an enzyme that can function to remove the cap structure from mRNA in S. cerevisiae (25,26). In contrast to the Dcp1/Dcp2 complex that preferentially functions on a cap with an N7 methyl moiety and release m 7 Gpp, Rai1 preferentially targets mRNAs with unmethylated caps and releases the entire cap structure GpppN, although it can function on a methylated cap to release m 7 GpppN to a lesser extent (26). Moreover, Rai1 also possesses the activity to hydrolyze the 5′ triphosphate of an uncapped RNA to release diphosphate and a monophosphorylated 5′-end RNA (25).…”
Section: ′ P Ends Located In Intronsmentioning
confidence: 99%
“…Cytoplasmic Xrn1 and nuclear Rat1 belong to a large family of conserved 5′-3′ exoribonucleases (33). Interestingly, Rat1 also forms a complex with a pyrophosphatase, Rai1, that was recently shown to cleave unmethylated capped RNA (34). Rai1 helps the exoribonuclease activity by stabilizing Rat1, and the catalytic activity of Rai1 is also dispensable for the activation of Rat1.…”
Section: Table 1 Dcs Family Proteins and Activation Of Exoribonucleamentioning
confidence: 99%